If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5 = 1x + 2 Reorder the terms: -5 + 4x = 1x + 2 Reorder the terms: -5 + 4x = 2 + 1x Solving -5 + 4x = 2 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -5 + 4x + -1x = 2 + 1x + -1x Combine like terms: 4x + -1x = 3x -5 + 3x = 2 + 1x + -1x Combine like terms: 1x + -1x = 0 -5 + 3x = 2 + 0 -5 + 3x = 2 Add '5' to each side of the equation. -5 + 5 + 3x = 2 + 5 Combine like terms: -5 + 5 = 0 0 + 3x = 2 + 5 3x = 2 + 5 Combine like terms: 2 + 5 = 7 3x = 7 Divide each side by '3'. x = 2.333333333 Simplifying x = 2.333333333
| (9x-2)+(2x+5)+(-7x-3)= | | 5(x-3)+6=5-9 | | 5*x-8+43= | | 3(5v+7)=126 | | (3x-2)+(x+2)+(-6x-1)= | | 0=-16x^2+127x | | -5x+3=-1 | | A=288 | | 2200=9*120+870+5c | | (3x-2)+(2x+9)= | | x+(x+2)+(x+4)=39 | | 6(2v)=6v^2 | | .6(.9)= | | 2200=450*2+450+m | | (4x-7)+(x-9)= | | 22=6+4s | | 3(x-4)=3x+24 | | 80+70=3x | | 2200=450*3+m | | 5(8a+9)=-35+4a | | -3[2x-(x+7)]= | | 3n-9n=-19 | | (16b-7)-5(3b+1)=-5 | | 25+7-1=30+1 | | 3(x-5)-12=2(x-2)+3 | | 6.28=6.28x | | -4+7(1-8x)=16 | | 6-g=15 | | 800=120*3+40r | | -(x-2)+3x=24 | | 12.56=6.28x | | 2x+45+25=4x |